Cerebrovascular Ultrasonography for Selecting Patients for Stroke Intervention - K. Sharma, Vijay; Yohanna, Kusuma; Kawnayn, Ghulam; Sarkar, Nabin; Batra, Amit (Recent Patents on CNS Drug Discovery (Discontinued), 2013)
Currently employed diagnostic ultrasonography provides clinically relevant information about cerebral hemodynamic changes in patients with cerebrovascular ischemia. The information thus obtained is often helpful to the physician for establishing or confirming the diagnosis and prognosis as well as in taking appropriate therapeutic decisions. It is associated with a high temporal resolution and can be performed bedside for rapid diagnosis as well as prolonged monitoring. Transcranial Doppler (TCD) ultrasonography is a non-invasive diagnostic modality that provides physiological information regarding various intracranial hemodynamic alterations in patients with cerebrovascular ischemia. Extended applications of TCD are useful in understanding various pathophysiological mechanisms responsible for the clinical manifestations of cerebrovascular ischemia. Thus, TCD is aptly called as the ‘stethoscope’ of a stroke neurologist. Cerebrovascular ultrasonography is considered as an essential component of a comprehensive stroke center. We have reviewed various recent patents pertaining to the applications of cerebrovascular ultrasonography employed in the selection of stroke patients for various therapeutic interventions.
Keywords: transcranial Doppler